Managers profile diversity as a strategic lever for value creation: a focus on accounting conservatism in Brazilian and French companies - Degenhart, Larissa; Barbosa, Edmery Tavares; Silva, Marcia Zanievicz da (Revista de Administração da UFSM, 2021)
Purpose – The research aimed to analyze the relationship between the diversity of the managers' profile as a lever for value creation and the accounting conservatism of Brazilian and French companies. Design/methodology/approach – The sample consisted of 71 Brazilian companies and 67 French companies, listed in the B3 Index IBrX-100 and the SBF 120 Index of Euronext Paris, respectively. Multiple Regression was used to analyze the data (2011 to 2015). Findings – The results revealed that the characteristics of the diversity of the profile of Brazilian managers that are related to accounting conservatism are: age, place of formation and position occupied in the directive body. In France, the characteristics are: degree of schooling, link with the company and function performed. Research limitations/implications – The limitation of the impossibility of generalizing the results is highlighted. As theoretical contributions, this research analyzes an element that can be considered for analysis in the face of accounting conservatism: the profile of managers. Practical implications – The diversity of the managers' profile should be considered in companies, since it has repercussions on accounting conservatism, that is, on how managers conduct accounting to maximize company value. Social implications – The findings have social implications for professionals who aim to enter the Brazilian and French labor market. Originality/value – The study advances in the accounting area, as it analyzes the governing body of organizations, an important differential in the analysis of the demographic, professional and performance characteristics of managers and their relationship with accounting conservatism.